Presentazione: Forme ed estetiche del disgusto (Itinera, 2024)
The present issue of Itinera collects the results and in-depth elaborations of the papers that were presented during the Graduate Conference Forms and Aesthetics of Disgust, held on 12 and 13 December 2023 at the University of L'Aquila, organised by a group of PhD students from the PhD programme in Literature, Arts and Media: Transcoding. During the conference, the notion of disgust was framed in its rich complexity and transversality, sifted through aesthetic-philosophical terms and those of representation and representability.
Keywords: Disgust; aesthetics; representation; limit